Globalization of foreign investment in Africa : the role of Europe, China and India. - Bodomo, Adams (Emerald Group Publishing, 2017)
The 21st Century era of globalization has opened up many investment alternatives for Africa. This book examines the role of FDI in Africa's socio-economic development with reference to Europe and two economic powers in Asia - China and India.